2021
DOI: 10.1002/admi.202101596
|View full text |Cite
|
Sign up to set email alerts
|

Laser Direct Writing of Highly Ordered Two‐Level Hierarchical Microstructures for Flexible Piezoresistive Sensor with Enhanced Sensitivity

Abstract: With the development of micro‐nano manufacturing technology, various hierarchical microstructures (HMs) are used to improve the sensitivity and measurement range of flexible pressure sensors. However, the fabrication of highly ordered HMs in simple, fast, and low‐cost ways remains a great challenge. In this work, laser direct writing technology is used to fabricate highly ordered HMs to enhance the sensitivity of flexible piezoresistive sensors. The HMs show a lateral expansion with the increasing pressure due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…The initial resistance of the uncompressed sensor can be calculated by where , , and represent the contact resistance between the bottom of the sensitive layer and electrodes, the resistance of the electrodes and the bulk resistance of the sensitive layer, respectively. By applying a certain load to the upper electrodes, the contact resistance between the upper electrodes and sensitive layer, which is defined as , becomes crucial to the sensing sensitivity, while the above resistances remain nearly constant and are considerably smaller than , which means they can be ignored 28 . By rewriting the sensitivity in terms of and the pressure change , the sensitivity can be expressed as where and are the initial and compressed contact areas, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial resistance of the uncompressed sensor can be calculated by where , , and represent the contact resistance between the bottom of the sensitive layer and electrodes, the resistance of the electrodes and the bulk resistance of the sensitive layer, respectively. By applying a certain load to the upper electrodes, the contact resistance between the upper electrodes and sensitive layer, which is defined as , becomes crucial to the sensing sensitivity, while the above resistances remain nearly constant and are considerably smaller than , which means they can be ignored 28 . By rewriting the sensitivity in terms of and the pressure change , the sensitivity can be expressed as where and are the initial and compressed contact areas, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The passive design of irregular microstructures with multiscale hierarchical properties offers an optimal solution for realizing continuous deformation with pressure 20,21 . Previously, methods of inverting naturally occurring microstructural templates (e.g., pollen grains 22 or petals 23 , human skin 24,25 , abrasive paper 26 , and kirigami patterns 27 ) or MEMS-fabricated artificial patterns [28][29][30][31] have been introduced for piezoresistive sensors to fabricate active layers. For example, Geng et al reported an ordered multilevel microstructure and explored the regulations of its radius and spatial distribution impacting the sensor performance merely via simulations and experiments 32 , rather than from a quantitative perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the sensor’s current rises with higher applied pressure. Nevertheless, when a certain load is applied, the bulk resistance remains relatively constant and significantly smaller than the contact resistance , (Figure S4), rendering it negligible. The sensitivity of a piezoresistive sensor is defined as S = (Δ I / I 0 )/Δ P , and by considering only R f , this equation can be expressed as S = normalΔ I / I 0 normalΔ P = ( U R f U R f 0 ) / U R normalf 0 normalΔ P = R normalf 0 R 1 normalΔ P = A A 0 1 normalΔ P = ( Δ A / A 0 ) / normalΔ P where Δ P is the pressure change applied to the sensor, R f0 and R f are the initial contact resistance and the contact resistance after pressure is applied, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…6b). 164 In addition, Li et al used a customizable laser marking technology approach to construct new hierarchical structures of FPSs. 165 Geng et al also realized the design and fabrication of multilevel microstructures by setting laser processing process parameters to control the diameter and height of multilevel microstructures.…”
Section: Preparation Of Mmssmentioning
confidence: 99%